2011
DOI: 10.5398/medpet.2011.34.3.155
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Garlic Extract Against some Pathogenic Animal Bacteria

Abstract: Cow urine therapy and all traditional practices from Indian systems of medicine have a strong scientific base. The cow has proved to be a boon in the areas of agriculture, science and technology, industry, energy, medicine etc for the development of any nation, in addition being eco-friendly in nature. In the present study the antibacterial potentials of cow urine were investigated. Total 14 pathogenic and non-pathogenic bacterial cultures were used as test organism against 10 different cow urine samples. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
5
3
0
3
Order By: Relevance
“…The findings of the current study are consistent with those of Safithria et al (2011) who found garlic extract inhibited the growth of E. coli. Other studies also showed that phytochemicals in garlic have strong antibacterial properties to combat E. coli, Salmonella, (Johnson and Vaughn, 1969), C. botulinum (DeWit et al, 1979), and other pathogenic species.…”
Section: Resultssupporting
confidence: 92%
“…The findings of the current study are consistent with those of Safithria et al (2011) who found garlic extract inhibited the growth of E. coli. Other studies also showed that phytochemicals in garlic have strong antibacterial properties to combat E. coli, Salmonella, (Johnson and Vaughn, 1969), C. botulinum (DeWit et al, 1979), and other pathogenic species.…”
Section: Resultssupporting
confidence: 92%
“…The ethanolic extract has mild inhibition compared to the aqueous extract. This result is similar to the findings of [26] that showed that the antibacterial activity of ethanol extract was mild compared to the aqueous extract and that there was no inhibition of garlic on S. aureus. Ethanolic onion extract showed antimicrobial activity against E. coli, S. aureus and K. pneumoniae with zones of inhibition ranging from 11mm-17mm (figure 4-6).…”
Section: Discussionsupporting
confidence: 91%
“…Staphylococcus aureus (S. aureus) juga berperan dalam keamanan pangan karena dapat menyebabkan kejadian mastitis pada sapi perah dan berpotensi mengkontaminasi produk susu sapi (Safithri et al, 2011). S. aureus merupakan bakteri fakultatif anaerob Gram positif, berbentuk bulat, menghasilkan enterotoksin, ditemukan di udara, debu, limbah, air, susu, makanan atau peralatan makan dan pada permukaan lingkungan (Wertheim et al, 2008).…”
Section: Pendahuluanunclassified